PENGARUH INFLASI, BI RATE DAN KURS TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) PERIODE 2013-2022 - Ramadhan Tri Undoko, Gilang; Hermawan, Hengki (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of inflation, BI Rate and Exchange Rate on the Composite Stock Price Index (IHSG) for the 2013-2022 period. The research method used in this research is descriptive with a quantitative approach. Data analysis used includes: Descriptive Statistical Test, Normality, Multicollinearity, Heteroscedasticity, Autocorrelation, Multiple Linear Regression, t Test (Partial), F Test (Simultaneous), Correlation Coefficient (R) and Determination Coefficient (R2). Based on the results of partial research using the t test, inflation has no and significant effect on the IHSG with a significance value of 0.204 > 0.05 with a calculated t value of 1.427 < t table 1.943. The results of the research show that the BI Rate has a significant and significant effect on the IHSG with a significance value of 0.038 < 0.05 with a calculated t value of -2.653 > t table 1.943 and the exchange rate has a significant effect on the IHSG with a significance value of 0.023 < 0.05 with a calculated t value of 3.036 > t table 1.943. Simultaneous test results for the influence of Inflation, BI Rate and Exchange Rate show that there is an influence and it is significant with a significance value of 0.013 with a calculated F value of 8.776 > F table 4.76. The results of the coefficient of determination test show an R square (R2) value of 0.814 or 81.4%, this shows that inflation, BI Rate and Exchange rate together contribute to IHSG of 81.4% while 19.6% is influenced by other variables. not examined in this study.